Information theory and the central limit theorem - Johnson, Oliver (Oliver Thomas) (Imperial College Press ; Distributed by World Scientific Pub., 2004)
This book provides a comprehensive description of a new method of proving the central limit theorem, through the use of apparently unrelated results from information theory. It gives a basic introduction to the concepts of entropy and Fisher information, and collects together standard results concerning their behaviour. It brings together results from a number of research papers as well as unpublished material, showing how the techniques can give a unified view of limit theorems.